Pengembangan Budaya Sekolah Didasarkan Pada Konsep Ideal Pendidikan Berbasis Agama Menanamkan Keimanan Melalui Metode Dzikir - Tubagus Syihabudin (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
In formulating the goals of Islamic education, we must first know the nature of humans which will be the benchmark in formulating the goals of Islamic education, besides that, the view of life also becomes an influence in formulating educational goals so that with different views, the goals are different. In this paper, the author's view of life is Islam so that what the author conveys is all based on the author's view. The essence of the purpose of Islamic education is to make humans have hearts of faith and piety to God Almighty, so that in Islam the heart is the most special human element and must receive special treatment so that the heart develops into a good heart. In order for the heart to develop into a kind heart, it must contain kindness. God is the highest good. Therefore, in order for the heart to be kind, it must contain God so that God becomes king in that heart. When God has become king and fills the heart, then the heart will be good. Such a heart will be able to control humans in their every action. Faith is in the heart, not in the mind and others, when the heart is filled with faith, then the heart is only God, automatically that person's memory is only God and cannot be separated from remembering God, this condition is called dhikrullah